Reporting analysis for small medium enterprise via mobile / Nurhusna Ayob - Ayob, Nurhusna (2013)
Report and analysis are important for every manager in every company to look at in order to make future expectation in their business. There are variety of tools provided in the market nowadays to make report and analysis; somehow, the effectiveness doesn’t really match their needs. As the result, the report and analysis were inefficient and time allocations for manpower are wasted. This project proposed to make the report and analysis available on live data refresh and available in cross mobile platform. This project visualized the information of the business performance in friendly interactive layout. The visualized data were in charts, graphs and performance indicator to make ease of use to the user. Besides that, with the help of visualized data, user can adjust the data using what-if-analysis part. In whatif- analysis part, it let the user to measure their business for future runs. In order to make the dashboard available incross mobile platform, mobile hybrid approach had been used in this project to implement the application. As a result, this project make user more convenient when they can access to the data everywhere and at any time they want. However, since mobile hybrid approach is still new in the market, it is not really stable to be implemented in these days compared to the native approach. More researches need to be done in the future about enhancing the capability of Application Programming Interface (API) in mobile hybrid approach so that iOS platform can view flash component.